Scot mist - McPherson, Catriona, 1965- (McPherson, Catriona, 1965- Last Ditch mystery., 2022)
"March 2020 and Operation Cocker is a go! The owners of the Last Ditch Motel, with a little help from their friend Lexy Campbell, are preparing to support one another through the oncoming lockdown, offering the motel's spare rooms to a select few from the local area in need of sanctuary. While the newbies are settling in, an ambiguous banner appears demanding one of them return home. But who is it for? Lexy and her friends put a plan into action to ward off the perpetrator, but the very next night, a resident disappears and a message scrawled in human blood is found. As California shuts down, the Last Ditchers make another gruesome discovery. They tried to create a haven but now it seems as if everyone's in danger. Is the motel under attack from someone on the outside? Scary as that is, the alternative is worse by far."--Publisher.